From Compliance to Commitment: Mapping Teachers’ Cognitive and Emotional Responses to Curriculum Reform - Delfia Herwanis; Al Musanna; Septia Wahyuni; Rahmanita Zakaria; Maulida Maulida (Pusat Riset dan Inovasi Nasional, 2026)
This study examines educators' cognitive and emotional reactions to curriculum change via a Delphi-based Focus Group Discussion (FGD) with vice principals of senior secondary schools (SLTA level) in Aceh Tengah and Bener Meriah, Indonesia. Despite structural innovations in Indonesia's curriculum reform, including the Merdeka Curriculum and the Deep Learning method, implementation gaps remain at the school level. This study seeks to delineate how educators cognitively comprehend curriculum modifications and emotionally respond to their requirements, and how these reactions affect their commitment to implementation. Data were gathered through organized group discussions and reflective responses in a Delphi panel session, employing a qualitative descriptive methodology. The findings indicate two predominant cognitive orientations: (1) progressive acceptance, perceiving reform as essential and forward-looking, and (2) interpretative ambiguity, signifying challenges in implementing policy within classroom settings. Teachers exhibited a range of emotions, from optimism and a sense of professional vocation to exhaustion, administrative overload, and resistance stemming from established attitudes. The shift from compliance to commitment was significantly shaped by educators' fundamental values, introspective abilities, collaborative environment, and perceived institutional backing. The study presents a belief-centered transformation paradigm that incorporates cognitive clarity, emotional resilience, and professional learning communities as strategic mechanisms for enduring curriculum improvement. These findings enhance the discussion of teacher beliefs as a vital aspect of educational development in emerging areas.